Dandarense: o ensino de história local e a identidade periférica, em diálogo - Francisco Gonçalves de Almeida (2024)
This research explores the possibilities of using the history of the urban peripheries and seeks to contribute to citizen formation. The history of the Dandara occupation, in the peripheral region of Belo Horizonte, between the Céu Azul and Trevo neighbourhoods, is the focus of this research study. The methodology used was ethnography, to explore the daily life of the school, define the concepts and give voice to the subjects. Two semi-structured interviews were also conducted in which the formation of the identity of the periphery was analysed. The elaboration of the educational product is part of the research methodology, with analysis of participatory mapping in the classroom. The concepts of popular education are used to guide the proposed didactic activities. The objective of the research is to visualize the memory of the periphery in the school context. In addition, there was a constant search to analyse the school context and the overcoming of stigmas. The research was conducted at the Escola Estadual Deputado Álvaro Salles, Trevo neighbourhood.